Social and emotional loneliness among older people living in Nursing Homes in Spain: a cross-sectional study - Molas Tuneu, Miriam; Jerez Roig, Javier; Minobes Molina, Eduard; Coll Planas, Laura; Escribà Salvans, Anna; Farrés Godayol, Pau; Yildirim, Meltem; Rierola Fochs, Sandra; Goutan Roura, Ester; Bezerra de Souza, Dyego Leandro; et al. (Anales de Psicología / Annals of Psychology, 2023)
Loneliness, little studied in Nursing Homes (NHs), can affect physical and mental health. We aimed to analyze the factors associated with overall, social, and emotional loneliness in 65 residents of 5 NHs from Central Catalonia (Spain), and to verify its prevalence. The sample consisted of 81.5% women with a mean age of 84±7.13 years. The cross-sectional study included older adults aged 65 or over and with preserved cognitive status. De Jong Gierveld Loneliness Scale was used to assess overall loneliness and its subtypes; and sociodemographic and health-related variables were collected. The chi-square (or Fisher’s) test and logistic regression were used for bivariate and multivariate analysis respectively. Prevalence of overall loneliness was 70.7% (95%CI:58.2-81.4), social loneliness 44.6% (95% CI: 33.1-56.6) and emotional loneliness 46.2% (95% CI: 34.5–58.1). Overall loneliness was associated with lower perceived quality of life (Odds Ratio-OR = 5.52, 95% CI:1.25-24.38) and NHs with state subsidized places (OR = 0.19, 95% CI: .05-.74); social loneliness with having 0-1 children (OR = .25, 95% CI: .08-.77), and emotional loneliness with depression (OR = 4.54, 95% CI: 1.28-16.08) and urinary incontinence (UI) (OR = 4.65, 95% CI: 1.23-17.52). Loneliness was present in almost 71% of residents and was associated with type of NH and poorer quality of life, the emotional with depression and UI and the social one with having less than 2 children.